DEVELOPING RENAL NURSES' BUTTONHOLE CANNULATION SKILLS USING E‐LEARNING. Issue 1 (31st January 2014) - Blackman, Ian R.; Mannix, Trudi; Sinclair, Peter M.
SUMMARY Background It has previously been shown that nurses can learn clinical nursing skills by e‐learning (online), and that many variables will influence how well nurses adopt learned clinical skills using distance education. Objectives This study aimed to identify and measure the strength of those factors which would simultaneously influence registered nurses' (RNs') beliefs about their own learning about buttonhole cannulation, using e‐learning. Design An online Likert style survey consisting of a list of statements related to knowledge and skill domains considered crucial in the area of buttonhole cannulation was distributed to 101 RNs before and after completing an e‐learning programme. Participants were required to identify their current level of self‐confidence in relationship to each of the statements. Measurements Measures of RNs' self‐rated abilities to assess and implement buttonhole cannulation after completing a related e‐learning program were tested using a Partial Least Squares Analysis (PLS‐PATH) programme. Results The study's results strongly identify that the nurses' ability to meet both clinical and educational outcomes of the renal e‐learning module can be predicted by six variables, none of which are directly related to the participants' demographic or clinical backgrounds. Conclusion These findings support the use of e‐learning to teach clinical skills to RNs, and demonstrate the value of Partial Least Squares Analysis in determining influential learning factors.